Effect of thiamine pyrophosphate on ischemia-reperfusion induced oxidative damage in rat kidney - Altuner, Durdu (Medknow Publications & Media Pvt Ltd, 2013)
OBJECTIVES: The biochemical effects of thiamine pyrophosphate on ischemia-reperfusion (IR) induced oxidative damage and DNA mutation in rat kidney tissue were investigated, and compared to thiamine. MATERIALS AND METHODS: Rats were divided into four groups: Renal ischemia-reperfusion (RIR); thiamine pyrophosphate + RIR (TPRIR); thiamine + RIR (TRIR); and sham group (SG). RESULTS: The results of biochemical experiments have shown that malondialdehyde (MDA) levels in rat kidney tissue after TRIR and TPRIR treatment were 7.2 ± 0.5 (P > 0.05) and 3.3 ± 0.3 (P < 0.0001) μmol/g protein, respectively. The MDA levels in the SG rat kidney tissue and in RIR group were 3.6 ± 0.2 (P < 0.0001) and 7.6 ± 0.6 μmol/g protein, respectively. Total glutathione (tGSH) levels in TRIR, TPRIR, SG, and RIR animal groups were 2.2 ± 0.3 (P > 0.05), 5.8 ± 0.4 (P < 0.0001), 6.2 ± 0.2 (P < 0.0001), and 1.7 ± 0.2 nmol/g protein, respectively. In the TRIR, TPRIR, SG, and RIR animal groups; 8-hydroxyguanine (8-OHGua)/Gua levels, which indicate mutagenic DNA, were 1.75 ± 0.12 (P > 0.05), 0.93 ± 0.1 (P < 0.0001), 0.85 ± 0.08 (P < 0.0001), and 1.93 ± 0.24 pmol/L, respectively. CONCLUSIONS: It has been shown that thiamine pyrophosphate prevents increase in mutagenic DNA in IR induced oxidative damage, whereas thiamine does not have this effect.